Huberantha, a replacement name for Hubera (Annonaceae: Malmeoideae: Miliuseae) - Chaowasku T. (Springer London, 2015)
© 2015, The Board of Trustees of the Royal Botanic Gardens, Kew. A replacement generic name, Huberantha Chaowasku, is proposed for the recently described genus Hubera Chaowasku segregated from Polyalthia Blume because the name Hubera has been recommended to be treated as a later homonym of Huberia DC. (Melastomataceae) by the nomenclature committee for vascular plants. Consequently, new combinations of twenty-seven species presently recognised are made under Huberantha.